2023
DOI: 10.3934/math.2023954
|View full text |Cite
|
Sign up to set email alerts
|

Applications of linear regression models in exploring the relationship between media attention, economic policy uncertainty and corporate green innovation

Abstract: <abstract> <p>The media plays a dual role of "supervision" and "collusion" in governance mechanisms. This study investigates the impact of media attention and economic policy uncertainty on green innovation by analyzing A-share industrial listed enterprises data between 2011 and 2020. The results show that media attention can effectively promote green innovation and that this impact is significantly heterogeneous. Media attention significantly affects green innovation in non-state-owned enterpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…Increased corporate social responsibility and fewer financial limitations are two ways that media attention can support green innovation. Therefore, it is crucial to support businesses' green innovation by paying close attention to the media as an institutional subject [ 116 ]. Human economic behavior, the media, and social factors must be taken into account when making investment decisions, given that green finance is the foundation for the development of sustainable financing of environmental projects, enabling a green transition towards economic growth that will be long-lasting and establishing a foundation for maintaining macroeconomic stability based on the creation of fresh alternative finance sources [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased corporate social responsibility and fewer financial limitations are two ways that media attention can support green innovation. Therefore, it is crucial to support businesses' green innovation by paying close attention to the media as an institutional subject [ 116 ]. Human economic behavior, the media, and social factors must be taken into account when making investment decisions, given that green finance is the foundation for the development of sustainable financing of environmental projects, enabling a green transition towards economic growth that will be long-lasting and establishing a foundation for maintaining macroeconomic stability based on the creation of fresh alternative finance sources [ 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…The media's green concern can raise companies' awareness of environmental issues and promote their development and application of green technologies [48]. Meanwhile, ESG has attracted considerable attention from all facets of society as the public has become increasingly…”
Section: Media's Green Concernmentioning
confidence: 99%
“…Meanwhile, according to the resource base theory, the green subsidies given to companies by the government form their resources, and the resources that companies possess enable them to gain a competitive advantage [33]. As GI has the dual externalities of environmental protection and knowledge spillover [48,51], it leads to a lack of companies' investment willingness [52]. Shao & Chen (2022) also revealed that government's concern and support for companies' green development can facilitate the enhancement of companies' knowledge base and technology accumulation and that government environmental subsidies are one of the most conducive means to address the environmental protection externalities of GI [52].…”
Section: Government's Green Concernmentioning
confidence: 99%